2011
DOI: 10.1007/s00404-011-2157-6
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase, interleukin-1 beta and tumor necrosis factor alpha levels in mild preeclampsia

Abstract: Mild preeclampsia is found associated with higher ChT activity. This result suggests that activated macrophages play a role in the pathogenesis of preeclampsia. This suggestion needs to be confirmed in future studies with larger populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…Interestingly in the present study, levels of both TNF-α and IL-1β were significantly higher in the PE and PE-PTZ groups. Such an increase in inflammatory cytokines not only supports the concept of inflammatory mechanisms contributing to the pathogenesis of preeclampsia [10], [30], but also raises the possibility that such an increase may be contributory to the susceptibility to seizure activity in vivo in the PE-PTZ group. The significantly decreased TNF-α level in the PE-PTZ-Mg group compared to the PE-PTZ group is also consistent with this idea.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly in the present study, levels of both TNF-α and IL-1β were significantly higher in the PE and PE-PTZ groups. Such an increase in inflammatory cytokines not only supports the concept of inflammatory mechanisms contributing to the pathogenesis of preeclampsia [10], [30], but also raises the possibility that such an increase may be contributory to the susceptibility to seizure activity in vivo in the PE-PTZ group. The significantly decreased TNF-α level in the PE-PTZ-Mg group compared to the PE-PTZ group is also consistent with this idea.…”
Section: Discussionsupporting
confidence: 59%
“…The cytokines TNF-α and IL-1β are primarily produced by macrophages and in preeclampsia participate in abnormal extravillous trophoblast invasion [29], [30]. Tosun et al [31] recently showed that the serum level of TNF-α was significantly increased in preeclamptic patients, especially in severe preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β has previously been found to increase the production of TNF-α, IL-6, HCG, endothelia [10], [17], [25], which were proved to be associated with the development of PE. IL-1β may also involve in the oxidative stress linked with PE by stimulating the secretion of other lymphocytotropic cytokines and catabolic enzymes [26].…”
Section: Discussionmentioning
confidence: 93%
“…Detectable IL-6 was also associated with term preeclampsia and had borderline significance with all preeclampsia cases. IL-6 has been associated with preeclampsia in some [11, 12, 15, 17] but not all [8, 18, 19, 22] cross-sectional third trimester studies. In contrast, a nested case-control study of 71 women who developed subsequent preeclampsia and 71 matched (age, parity, and BMI) controls found no significant associations with IL-1β, IL-6, IL-10, TNF-α, or PAI-1 measured by ELISA at 18 weeks gestation [24].…”
Section: Discussionmentioning
confidence: 99%